Improving bottleneck features for Vietnamese large vocabulary continuous speech recognition system using deep neural networks - Nguyen, Bao Quoc; Vu, Thang Tat; Luong, Mai Chi (Journal of Computer Science and Cybernetics, 2016)
In this paper, the pre-training method based on denoising auto-encoder is investigated and proved to be good models for initializing bottleneck networks of Vietnamese speech recognition system that result in better recognition performance compared to base bottleneck features reported previously. The experiments are carried out on the dataset containing speeches on Voice of Vietnam channel (VOV). The results show that the DBNF extraction for Vietnamese recognition decreases relative word error rate by 14 % and 39 % compared to the base bottleneck features and MFCC baseline, respectively.